Whole genome sequencing analysis and biofilm formation in Salmonella Enteritidis PT4 578 - Carneiro, Deisy Guimarães (2022)
Salmonella is an important and versatile foodborne pathogen responsible for numerous infections and deaths worldwide. The difficulty of controlling and eradicating this pathogen is related to its ability to form complex aggregates of cells, called biofilms. In a biofilm, cells are surrounded by a matrix of self-produced extracellular polymeric substances that protect against various types of stress, such as desiccation, sanitization, and host defense. The Salmonella biofilm matrix is composed mainly of curli fimbriae and cellulose. A highly complex genetic network regulates the synthesis of these components. The main regulators associated with biofilm formation are the CsgD protein and the bis-(3'-5')-cyclic dimeric guanosine monophosphate (c-di-GMP), which activate the biosynthesis of most polymers. Quorum sensing, a cellular communication mechanism, is also described as an important regulator of biofilm formation in Salmonella. The objective of the present work was to sequence the genome of Salmonella enterica Enteritidis PT4 578, analyze the main characteristics related to virulence and biofilm formation, and compare the genome and morphotype formation, biofilm and motility phenotypes with four related serotypes. Furthermore, evaluate the influence of temperature, atmosphere, and quorum sensing on biofilm formation by this serotype. Genome analyzes showed that Salmonella Enteritidis PT4 578 has 165 virulence genes, representing 3.66% of the coding sequences. Twelve Salmonella pathogenicity islands (SPI) were identified, some extremely conserved, such as SPI1 and SPI2, that encode the apparatus of intracellular invasion and colonization,. A total of thirteen gene clusters related to fimbriae biosynthesis, including the csg operon, were also annotated. Under aerobic and anaerobic conditions, Salmonella Enteritidis PT4 578 can form a biofilm on stainless steel coupons at 28 °C and only under aerobic conditions at 37 °C. However, adding of N-hexanoyl homoserine lactone (C12-HSL) to the anaerobic culture medium reverses the biofilm formation phenotype at 37 °C. In this condition, C12-HSL increased the expression of the adrA gene, a diguanylate cyclase related to the synthesis of c-di-GMP and the luxS gene, which is part of another quorum sensing mechanism that uses autoinducer-2 (AI-2), present in Salmonella. Although it did not influence biofilm formation at 28 ºC, C12- HSL also increased luxS expression. The data presented here reinforce the role of conditions of atmosphere and temperature, as well as quorum sensing in Salmonella biofilm formation. Finally, it reports a possible connection between this pathogen's two main quorum sensing mechanisms. Understanding the factors that influence Salmonella biofilm formation can contribute to developing control and eradication strategies. Keywords: Genome analyses. Biofilm. Quorum sensing.